Design of a modular robotic system that mimics small fish locomotion and body movements for ethological studies. (26th May 2017) - Bonnet, Frank; Cazenille, Leo; Séguret, Axel; Gribovskiy, Alexey; Collignon, Bertrand; Halloy, José; Mondada, Francesco
Robotic animals are nowadays developed for various types of research, such as bioinspired robotics, biomimetics, and animal behavioral studies. The design of these robots poses great challenges as they often have to achieve very high-level performances in terms of locomotion, size, and visual aspect. We developed a robotic system for direct underwater interactions with small fish species. This robotic platform is composed of two subsystems: a miniature wheeled mobile robot that can achieve complex locomotion patterns and a robotic fish lure that is able to beat its soft caudal peduncle to generate fish-like body movements. The two subsystems are coupled with magnets that allow the robotic lure to reach very high speeds and accelerations, thanks to the mobile robot. We used zebrafish ( Danio rerio ) to model small fish locomotion patterns and construct a controller for the motion of our robotic system. We have demonstrated that the designed system is able to achieve the same types of motion patterns as the zebrafish while mimicking the body movements of the fish. These results define new standards for robotic fish lures and bring to the field of fish–robot interaction a new tool for ethological studies.